Binasal Occlusion for the Treatment of Visual Motion Sensitivity after Traumatic Brain Injury: A Case Series. - Posvar, Winston B.; Klein, Steven; Gutierrez, Jill M. Bakota; Capo-Aponte, Jose (Optometry & Visual Performance, 2019)
Background: Symptoms of visual motion sensitivity (VMS) secondary to traumatic brain injury (TBI) have previously been reported to improve with binasal occlusion (BNO). In previous literature, BNO has improved ambulation and gait in those with VMS. The aim of this case series was to demonstrate how BNO improves symptoms of VMS during ambulation in a military population with history of TBI. Methods: Three patients with a history of TBI and suspected VMS underwent a neurooptometric examination, including BNO applied to spectacles during ambulation in a clinical setting. Gait was subjectively evaluated by the examiner, and symptoms of VMS were assessed by the patient. Results: Subjective improvement in gait and symptoms of VMS were appreciated in three TBI patients with VMS. Two subjects also demonstrated improved versional function with BNO. All three subjects were subsequently prescribed BNO and neuro-optometric vision rehabilitation. One subject was lost to follow-up, and two subjects reported improved visual function with BNO several months after its initial application. Conclusion: BNO is an effective tool for treating VMS symptoms secondary to TBI. The effect of neuro-optometric vision rehabilitation in conjunction with BNO for VMS is yet to be determined.